Book Review: Achin Vanaik, ed., ICSSR Research Surveys and Explorations: Political Science. (June 2014) - Devare, Aparna
Achin Vanaik, ed., ICSSR Research Surveys and Explorations: Political Science. Four Volumes: 1. The Indian State (175 pages) 2. Indian Democracy (287 pages), 3. Indian Political Thought (276 pages), 4. India Engages the World (567 pages). New Delhi: Oxford University Press. 2013. ₹ 3, 995.